Developing the AIAT-HRM Model: A Conceptual Framework for Integrating Amanah, Ihsan, Adil, and Tanggung Jawab into Educator HRM Practices in Islamic Educational Institutions - Farhan Arif Alfarisi; Lepia Juniza; Fitri Arisanti; Samiyono Samiyono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study develops the AIAT-HRM Model as a conceptual framework for systematically integrating four core Islamic values (amanah (trustworthiness), ihsan (excellence), adil (justice), and tanggung jawab (responsibility)) into educator human resource management (HRM) in Islamic educational institutions. Existing HRM practices in these institutions remain fragmented and have not translated Islamic values into operational HRM mechanisms. Using a qualitative library research design and Jabareen’s (2009) conceptual analysis procedure, the study synthesizes normative-theological sources (the Qur’an and Hadith), scholarly literature on Islamic education management, and contemporary HRM frameworks. The findings demonstrate the model’s specific contributions: amanah transforms recruitment and selection through integrity-based screening; ihsan shapes professional development and performance appraisal through standards of excellence and reflective evaluation (muhasabah); adil informs proportional compensation and just appraisal; and tanggung jawab institutionalizes layered accountability across HR planning. The AIAT-HRM Model converts Islamic values from moral ideals into measurable HRM indicators, including transparent recruitment SOPs, 360-degree appraisal mechanisms, and syura-based planning protocols. Theoretically, this study advances value-based HRM by offering an integrative model that bridges Islamic ethics and functional HRM. Practically, it provides educational leaders with concrete steps to align recruitment, development, appraisal, and compensation with Islamic principles. Future research should empirically test the AIAT-HRM Model across pesantren, madrasah, and Islamic universities to assess its impact on educator performance and institutional effectiveness.